Tuvalu : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Tuvalu. (IMF Staff Country Reports; Country Report, 2021)
Swift implementation of containment measures, limited spillovers from tourism, and COVID-related fiscal spending financed by buoyant fishing revenues and donor grants have allowed Tuvalu-a fragile Pacific micro-state-avoid a recession in 2020. The economy is expected to expand by 2.5 percent in 2021, supported by fiscal expenditures and resumption of infrastructure projects. But significant challenges remain: Tuvalu is vulnerable to the effects of climate change, its economy is dominated by the public sector, and its revenue base is narrow. Uncertainty around donor commitments complicates fiscal planning.